A peer-to-peer IO buffering service based on RAM-grid. (9th November 2009) - Zhang, Yiming; Chu, Rui; Li, Dongsheng
The performance of IO-intensive applications is determined by the hit ratio of local disk cache and the IO latency of missed disk accesses. To improve the IO performance, in this paper we propose PIB, a peer-to-peer IO buffering service based on RAM-grid (a new grid system aiming at memory resource sharing in WAN). The PIB service acts as a two-level disk cache, which buffers obsolete blocks in idle nodes on the internet for IO-intensive applications. It reduces the IO latency of missed disk accesses by means of the speed advantage of network over disks, and improves the hit ratio of local cache based on accurate identification of IO patterns. The effectiveness of our proposals is demonstrated through the trace driven simulation studies.